Kontribusi Faktor-Faktor Pendorong Terhadap Penerapan PROPER di Perusahaan Pengolahan Kelapa Sawit di Propinsi Riau - Siregar, Rosita Erliwahyuni; Rasyad, Aslim; Hadi, Syaiful (Universitas Riau, 2016)
The objective of this study was to describe the implementation of Company Environmental Performance Programme (PROPER) on palm oil processing company in Riau Province and to analyze the effect of determining factors such as the announcement of company performance in the mass media, banking factor, global market demands, legal sanctions and the company's commitment to the implementation of the PROPER. Samples were selected at purposive random from palm oil processing plants located in Riau province which participated in PROPER in the year of 2013-2014. Data analysis were performed by multiple linear regression. The result shows that there was significant influence of the variables of the announcement in the mass media, banking factor, global market demands, legal sanctions and the company's commitment to environmental performance (PROPER). Variation of the independent variables (announcement in the mass media, banking factor, global market demands, legal sanctions and company’s commitment) could explain only 36.1% of the dependent variable (PROPER) while the remaining 63.9% is explained by other variables. Analysis of single determinant such as announcement in the mass media and global market demands has nonsignificantly positive effect on the environmental performance (PROPER). While the smooth provision of credit by banks and legal sanctions has non-significantly negative effect on the environmental performance (PROPER). On the other hand, the company's commitment in managing the environment has significant positive effect to the environmental performance (PROPER).